Lateral augmentation of the posterior edentulous mandible: A retrospective single arm comparison of ridge split, block bone grafts and guided bone regeneration. (2nd September 2021) - Nath Bera, Rathindra; Kumar Sharma, Naresh; Bhattacharjee, Bappaditya; Bhatnagar, Atul; Gopalakrishna Naveen Kumar, Puvvadi; Kusumakar, Ananta
Abstract: Background: A deficient hard and soft tissue at the surgical site is a definitive challenge for dental implant placement. Commonly used procedures for augmentation include block bone grafts, guided bone regeneration, distraction, ridge expansion, ridge split, sandwich osteotomy, etc. The current study evaluates three techniques employed for horizontal augmentation of the mandible. Methods: A retrospective chart review was conducted for patients reconstructed with either block bone (A), guided bone regeneration (B), or ridge split (C) for lateral augmentation of posterior mandible. The primary outcome variables assessed were immediate postoperative bone width and bone width after 4 months, bone gain and resorption. Complications were evaluated as secondary outcomes. ANOVA and post hoc turkey tests were used for statistical analysis. A p‐value of <0.05 was considered as statistically significant. Results: A total of 250 patient records were included in the study. Group C had a mean bone gain of 5.8649 ± 0.6520 mm statistically significant from others. Resorption was maximum in Group B 1.1612 ± 0.2821 mm. Iliac crest graft gave a mean 5.7285 ± 0.1823 mm bone gain. Overall no difference in bone gain between particulate or block interposition. Discussion: Grafts from intraoral sites are comparable in terms of resorption. ARS considerably provides better augmentation compared to GBR and onlays. Conclusion: Ridge split followed by onlay block bone grafting provides the best outcomes. Ramus and symphysis grafts are comparable. Iliac grafts are still the best for significant augmentations. Guided bone regeneration suffers maximum resorption.